PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL DALAM MENDORONG BUDAYA KERJA PASCA PENERAPAN WFH DAN WFO DI MASA PANDEMI COVID-19 - Ni Putu Eka Sutiasih; Ni Wayan Ari Sudiartini; Ni Putu Yuli Tresna Dewi (Nusantara Hasana Journal, 2022)
The quality of human resources can be fulfilled if job satisfaction as an element that affects performance can be created perfectly. The individual productivity of a worker when virtual work can be very different from working in an office or Work from Office (WFO) and not all work can be done at home and done optimally. While the transactional leadership style focuses on completing tasks and goals, exchanging praise or appreciation for achieving these goals, and anticipating deviations in the process of achieving tasks. So it is necessary to do alignment between leadership styles to obtain a good work culture. This study aims to determine the Effect of Transformational and Transactional Leadership in Encouraging Work Culture after the Implementation of WFH and WFO in the Covid-19 Pandemic Period. The analytical method used is the classical assumption test and multiple linear regression analysis. The results show: Transformational Leadership has a positive effect on work culture, meaning that the higher Transformational Leadership, it will affect the improvement of Work Culture. Transactional Leadership has a positive effect on work culture, meaning that the higher Transactional Leadership, it will have an effect on increasing Culture. Work. Transformational Leadership and Transactional Leadership simultaneously affect work culture, meaning that the greater the Transformational Leadership and Transactional Leadership, the greater the impact on Work Culture.